Unaccompanied Minors in France and Inequalities in Care Provision under the Child Protection System - Isabelle Frechon; Lucy Marquet (Social Work & Society, 2018)
The issue of unaccompanied minors (UAM) is frequently front-page news in France, against a background of economic recession and increasing flows of migrants through Europe. The worry these situations arouse combines with concerns about the fate of unaccompanied minors. Since 2010, the legislation has been constantly changing to adapt care arrangements to the increase in numbers of unaccompanied minors entering the country. The French child protection system is organized by département. France is divided into 96 départements in Metropolitan France and 5 in Overseas France. Each département finances and conducts its own child protection policy within the framework of the national legislation. The cost of care for unaccompanied minors is the core issue, far ahead of the question of what support they must be given. The real number of unaccompanied minors is therefore not really known, because only those recognized as such can be counted. In this paper we describe the assessment process that filters and sorts this population group at each stage and then present the findings of a study of the living conditions of children in care, including unaccompanied foreign minors.